ASPEK KNOWLEDGE MANAGEMENT TERHADAP KINERJA KARYAWAN MELALUI KEUNGGULAN BERSAING KANTOR PUSAT PT. BANK SULSELBAR - Arham Nawawi; Haris Maupa; Muhammad Ismail (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
The strategy of knowledge management becomes a primary vehicle for organizations achieve their goals, and to compete with good. The study aims to (1) find out the influence of the quality of learning on performance of employees of PT. Bank Sulselbar. (2) know the influence of the knowledge management process on performance of employees of PT. Bank Sulselbar. (3) find out the influence of the knowledge-sharing process on performance of employees of PT. Bank Sulselbar. (4) find out the influence of innovation against the performance of the employees of PT. Bank Sulselbar. (5) find out the influence of the quality of learning against competing superiority of PT. Bank Sulselbar. (6) know how the process of management of knowledge against the competitive advantage of PT. Bank Sulselbar. (7) find out the influence of the knowledge-sharing process against competing superiority of PT. Bank Sulselbar. (8) Knowing the influence of innovation against competing superiority of PT. Bank Sulselbar. (9) find out the influence of competitive advantage against the performance of the employees of PT. Bank Sulselbar. In this study researchers using experimental research using appropriate research methods and emphasis on the analysis of data in the form of the ordinal numbers are processed with statistical methods. Data collection methods used in this research is a Library Research, and Feel research. The technique of analysis used in this study is to test the validity, reliability testing, descriptive analysis, and path analysis. The results of this study suggest that (1) the quality of learning significant effect on performance of employees. (2) knowledge management processes significant effect on performance of employees. (3) the process of knowledge sharing effect significantly to the performance of the employee. (4) Innovation has no effect on performance of employees. (5) the quality of learning effect significantly to the competitive advantage of employees. (6) knowledge management processes significant competitive advantage against influential employees. (7) the process of knowledge sharing effect significantly to the competitive advantage of employees. (8) the innovation has no effect against the competitive advantage of employees. (9) the competitive advantage of significant effect on performance of employees